Investigating the Perovskite Ag1-3xLaxNbO3 as a High-Rate Negative Electrode for Li-Ion Batteries - Le Calvez, Etienne; Espinosa-Angeles, Julio César; Whang, Grace J.; Dupré, Nicolas; Dunn, Bruce S.; Crosnier, Olivier; Brousse, Thierry (Frontiers in Chemistry, 2022)
The broader development of the electric car for tomorrow's mobility requires the emergence of new fast-charging negative electrode materials to replace graphite in Li-ion batteries. In this area, the design of new compounds using innovative approaches could be the key to discovering new negative electrode materials that allow for faster charging and discharging processes. Here, we present a partially substituted AgNbO3 perovskite material by introducing lanthanum in the A-site. By creating two vacancies for every lanthanum introduced in the structure, the resulting general formula becomes Ag1-3xLax󠄀□2xNbO3 (with x ≤ 0.20 and where □ is a A-site vacancy), allowing the insertion of lithium ions. The highly substituted Ag0.40La0.20□0.40NbO3 oxide shows a specific capacity of 40 mAh.g-1 at a low sweep rate (0.1 mV.s-1). Interestingly, Ag0.70La0.10□0.20NbO3 retains 64% of its capacity at a very high sweep rate (50 mV.s-1) and about 95% after 800 cycles. Ex situ 7Li MAS NMR experiments confirmed the insertion of lithium ions in these materials. A kinetic analysis of Ag1-3xLax󠄀□2xNbO3 underlines the ability to store charge without solid-state ion-diffusion limitations. Furthermore, in situ XRD indicates no structural modification of the compound when accommodating lithium ions, which can be considered a zero-strain material. This finding explains the interesting capacity retention observed after 800 cycles. This paper thus demonstrates an alternative approach to traditional insertion materials and identifies a different way to explore not-so common electrode materials for fast energy storage application.